1989
DOI: 10.1159/000125163
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Central LHRH on LH Secretion in the Ovariectomized Ewe

Abstract: The role of central luteinizing hormone releasing hormone (LHRH) in the control of pulsatile LHRH and luteinizing hormone (LH) secretion was investigated in ovariectomized adult ewes. Injection of LHRH (2.1–21 pmol) into the third cerebral ventricle caused a delayed but sustained inhibition of LH secretion. Pulse frequency, pulse amplitude and mean LH levels were reduced significantly when compared with the responses to the control injection of saline (50 µl). The inhibitory effect of centrally administered LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
2
26
3
Order By: Relevance
“…The results in OVX rats are quite different from those of other researchers who have shown decreases in LH secretion following intracerebroventricular injections of LHRH in OVX rats [1,2,3] and ewes [4]. The difference in the results is probably related to the difference in the injection site.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The results in OVX rats are quite different from those of other researchers who have shown decreases in LH secretion following intracerebroventricular injections of LHRH in OVX rats [1,2,3] and ewes [4]. The difference in the results is probably related to the difference in the injection site.…”
Section: Discussioncontrasting
confidence: 98%
“…Taking these results together with our previous report, the present study indicates that 1) endogenous LHRH in the MPO is involved in the ultra-short feedback regulation of LHRH release and 2) the ultra-short positive feedback mechanism in the MPO acts at the time of the proestrous LH surge but not under a hormonal milieu as in ovariectomized rats. Key words; LHRH, Preoptic area, Feedback, LH, Ovariectomy, LHRH antagonist (Endocrine Journal 41: 559-563,1994) IT HAS BEEN reported that intraventricular injection of LHRH or LHRH agonist reduces the secretion of LHRH [1] and thus the secretion of LH is decreased in ovariectomized (OVX) rats [2, 3] and ewes [4], implying the existence of an ultra-short negative feedback mechanism for the control of LHRH secretion. In addition, in vitro studies have suggested that the neural structure that is involved in the mechanism is in the mediobasal hypothalamus including the median eminence [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological significance of endogenous LHRH in regulating the release of LHRH ('ultrashort'-loop feedback) has been examined using a median eminence preparation in vitro (6). In the presence of an LHRH antagonist, basal secretion of LHRH increased in a dose-related manner suggesting that endogenous LHRH may exert a tonic inhibitory influence on its own release.In the sheep, the inhibitory action of exogenous LHRH may be reversed by the central administration of an LHRH antagonist (1) suggesting that a specific interaction with an LHRH receptor, rather than a non-specific effect, is involved. Although an interaction with a central LHRH receptor is postulated, the LHRHinduced inhibition was delayed (1 to 3 h following injection) and sustained (up to 20 h following injection).…”
mentioning
confidence: 99%
“…In the sheep, the inhibitory action of exogenous LHRH may be reversed by the central administration of an LHRH antagonist (1) suggesting that a specific interaction with an LHRH receptor, rather than a non-specific effect, is involved. Although an interaction with a central LHRH receptor is postulated, the LHRHinduced inhibition was delayed (1 to 3 h following injection) and sustained (up to 20 h following injection).…”
mentioning
confidence: 99%